Patient-specific numerical investigation of the correction of cervical kyphotic deformity based on a retrospective clinical case - Wu, Tianchi; Chen, Hongyu; Sun, Yu; Xia, Tian; Zhou, Feifei; Lu, William W. (Frontiers in Bioengineering and Biotechnology, 2022)
Little research has been reported on evaluating the safety of the fixation construct in cervical kyphosis correction. In this study, we proposed a principal-strain criterion to evaluate the safety of the fixation construct and validated the modeling method against a retrospective case of anterior cervical discectomy fusion (ACDF). From C2 to T2 vertebra bodies, fixation instruments were reconstructed and positioned as per postoperative computed tomography (CT) scans. Head weight (HW) and various moments estimated from isometric strength data were imposed onto the C2. The postoperative stability of non-surgical segments, deformations surrounding the screw trajectories, and contact slipping on zygapophysial joints were analyzed. The model was validated against the reality that the patient had a good fusion and deformity correction. The ACDF restricted the range of motions (ROMs) of cervical segments and lent stability to vertebra fusion, no failure was found in the finite element (FE) model of cervical vertebrae. The deformation surrounding the screw trajectories were concentrated to the lateral sides of trajectories, recommending that the shape of the anterior cervical plate conforming to the curvature of the vertebra and screws fully inserted into vertebrae reduced the deformation concentration around the screw trajectories.